Defect-Induced Photoluminescence Blinking of Single Epitaxial InGaAs Quantum Dots - Hu, Fengrui (Sci Rep, 2015)
Here we report two types of defect-induced photoluminescence (PL) blinking behaviors observed in single epitaxial InGaAs quantum dots (QDs). In the first type of PL blinking, the “off” period is caused by the trapping of hot electrons from the higher-lying excited state (absorption state) to the defect site so that its PL rise lifetime is shorter than that of the “on” period. For the “off” period in the second type of PL blinking, the electrons relax from the first excited state (emission state) into the defect site, leading to a shortened PL decay lifetime compared to that of the “on” period. This defect-induced exciton quenching in epitaxial QDs, previously demonstrated also in colloidal nanocrystals, confirms that these two important semiconductor nanostructures could share the same PL blinking mechanism.